High loading dose of clopidogrel in patients undergoing percutaneous coronary intervention - Grajek, Stefan; Lesiak, Maciej (Przewodnik Lekarza/Guide for GPs, 2005)
In recent years in Poland a great development of interventional treatment of patients with acute coronary syndromes (ACS) has been seen. Since the publication of the CURE study, on the treatment of ACS patients, and the analysis of a subgroup treated with percutaneous coronary intervention (PCI) a loading dose of 300 mg of clopidogrel has become a routine practice. The later studies though, revealed that such a dose, given immediately before or during the intervention is not sufficient to reduce significantly the risk of periprocedural ischemic complications. One of the possible solutions may be to delay the intervention for several hours after clopidogrel pretreatment. Since in the most of ACS patients a clear benefit of immediate intervention has been demonstrated, the new studies on the higher dosing were started. Those studies, including low- as well as high-risk patients undergoing PCI in stable angina or in non-ST elevation ACS revealed a significant advantage of a loading dose of 600 mg, with acceptable risk of bleeding complications. Although none such a study (with a dose of 600 mg) has been performed yet in patients with ST elevation ACS, the two recent studies have demonstrated significant advantage of clopidogrel 300 mg over placebo , and there is no reason to claim that the higher dose will be not beneficial in this high-risk population. In the last ESC PCI guidelines there is a recommendation IC that a clopidogrel loading dose of 600 mg should be preferred in patients, both with and without ST-elevation ACS if pretreatment with the drug can not be initiated at least 6 hours prior to intervention. Given the efficacy and safety of the higher dose of clopidogrel, we are convinced that in the „real world” setting, the best option could be a prehospital pretreatment with 600 mg of clopidogrel in all ACS patients.